ANALISIS TOKOH PEREMPUAN DALAM NOVEL BUMI MANUSIA KARYA PRAMOEDYA ANANTA TOER (Sebuah Kajian Feminisme Dilihat dari Karakter, Konflik, dan Sikap Tokoh) - Arief Darmawan; Aan Sugiantomas (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2014)
The characteristic of literary work is which it can crystalized message by implicit or explicit way and submit it continously as long as it appreciated by readers. One of the literary work, the novel titled Earth of Mankind (Bumi Manusia) by Pramoedya Ananta Toer is tipically different because it has man main figure, but contains feminism spirit. Therefore, researcher analyze the novel. The problem formulations are: 1) who are the women figure in the novel Earth of Mankind by Pramoedya Ananta Toer?; 2) how is the character of women figure in the novel Earth of Mankind by Pramoedya Ananta Toer?; 3) how is the conflict that experienced by women figure in the novel Earth of Mankind by Pramoedya Ananta Toer?; 4) how is the demeanor of women figure up against the conflict in the novel Earth of Mankind by Pramoedya Ananta Toer?; 5) what is the feminism substance in the novel Earth of Mankind by Pramoedya Ananta Toer? The research objectives are: 1) to know the women figure in the novel Earth of Mankind by Pramoedya Ananta Toer; 2) to know the character of women figure in the novel Earth of Mankind by Pramoedya Ananta Toer; 3) to know the conflict that experienced by women figure in the novel Earth of Mankind by Pramoedya Ananta Toer; 4) to know the demeanor of women figure up against the conflict in the novel Earth of Mankind by Pramoedya Ananta Toer; 5) to know the feminism substance in the novel Earth of Mankind by Pramoedya Ananta Toer. The Method of this research is Analytic Descriptive Method. The Data Acquiring Technic is Documentation Technic. Research Source is the novel Earth of Mankind by Pramoedya Ananta Toer. After the research of the novel has done, researcher take the conclusion that: 1) women figures in this novel are Nyai Ontosoroh, Annelies Mellema, and Julia Magda Peters; 2) the character of women figure in this novel is different and represent woman on each job and social status. Nyai Ontosoroh is knowledgeable and has authority, Annelies Mellema is a crybaby and spoiled, Julia Magda Peters is a smart person and a motivator, 3) the conflict in this novel is dominated by Nyai Ontosoroh; 4) the demeanor of women figure to face the conflict is different depend on characteristic and knowledge of the woman figure; 5) feminism subtances in this novel are different from each woman figure depend on their characters, conflicts, and acts to solve the conflicts.Keyword : feminism, character, conflicy, women figure, prose Bumi Manusia